Coaches` perceptions of long-term potential are biased by maturational variation - Cripps, A. J.; Hopper, L. S.; Joyce, C. (International Journal of Sports Science & Coaching, 2016)
Talent identification and development programs seek to recognise and promote athletes with long-term potential in a particular sport. Coaches involved in these programs are often required to make inclusion or exclusion decisions based on their perceptions of an athlete`s long-term potential. However, biological maturity can influence physical capabilities of adolescent athletes and may bias coaches` perceptions of long-term potential. This study explored the relationship between coaches` perceptions of long-term potential and variations in athlete`s biological maturity. Talented adolescent male Australian footballers (n=264) from nine different teams were recruited to provide basic anthropometric information for estimates of biological maturity. Coaches from each team were recruited to provide a rating of their own player`s long-term potential. Coaches perceived late maturing athletes to have a significantly lower long-term potential than their average (x2=9.42, p<0.01) and early (x2=5.86, p=0.04) maturing counterparts. Of the late maturing athletes, 72% were predicted to go no further than adolescent competition. No concurrent bias was evident between the average or early maturing athletes. The findings of this study demonstrate coaches' perceptions of long-term potential can be biased by maturational variation in adolescent athletes. Such perceptual bias may impact on coaches selection decisions and result in talented but late maturing athletes missing selection into development pathways. ABSTRACT FROM AUTHOR